Factor influencing attitude towards online shopping in Pasir Mas Kelantan / Muhammad Taqiuddin Ahmad Tajudin - Ahmad Tajudin, Muhammad Taqiuddin (2019)
This study consists of five chapters, Chapter one consists of Introduction. Chapter two consist of literature review, chapter three containing threoretical framework and research methodology, chapter four consists of analysis and interpretation of data and chapter five contains the discussion about the result of the topic and chapter six consists of conclusion and recommendation. This study was conducted to find out the factor such as convenience, website design, time saving and security with the consumer attitude toward online shopping in Pasir Mas, Kelantan. By investigating all these factors, the researcher will able to know the most critical factor contributes to consumer attitude toward online shopping in Kelantan, specifically in Pasir Mas. The respondents were public sector government workers, customer in supermarket and student with the total of 384 respondents. The researcher used simple random sampling technique in order to collect the data from the distributed questionnaires. Later, the researcher used the Statistical Package for Social Science (SPSS) to analyze all the collected data. The finding then were discussed and a few recommendation and suggestion for future research were stated.